International Oil Conference and Exhibition in Mexico 2006
DOI: 10.2118/104004-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pressure in a Well With a Vertical Fracture With Variable Conductivity and Skin Fracture

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractA mathematical model was developed to study the behavior of a well with variable finite-conductivity and skin fracture, for a vertical fracture in an infinite slab reservoir.The solution is valid for slightly compressible fluid and gas fluid applying the pseudo-pressure concept. The constant rate with wellbore storage and constant pressure are the production modes considered. Curves type are used to showsthe effect of the changes of conductivity and skin near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…It is shown that results from our solutions agree very well with those reported in the literature (Guppy et al 1982;Poe et al 1992). In this study, we focus on the latter two issues by proposing a semianalytical solution to discuss the transient-pressure behaviors of a varying-conductivity fracture under non-Darcy-flow condition.…”
supporting
confidence: 85%
See 4 more Smart Citations
“…It is shown that results from our solutions agree very well with those reported in the literature (Guppy et al 1982;Poe et al 1992). In this study, we focus on the latter two issues by proposing a semianalytical solution to discuss the transient-pressure behaviors of a varying-conductivity fracture under non-Darcy-flow condition.…”
supporting
confidence: 85%
“…To account for the high-velocity flow in the fracture, the following Forchheimer equation will be used (Guppy et al 1982): To account for the high-velocity flow in the fracture, the following Forchheimer equation will be used (Guppy et al 1982):…”
Section: Model Of a Varying-conductivity Fracture With Darcy Flowmentioning
confidence: 99%
See 3 more Smart Citations